2011
DOI: 10.1021/la203433z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Complementary Recognition of Supramolecular Urea–Aminotriazines in Solution and on Surfaces

Abstract: The recognition of self-complementary quadruple urea-aminotriazine (UAT)-based hydrogen-bonded arrays was investigated in solution and at surfaces. For this purpose, an UAT-based donor-acceptor-donor-acceptor (DADA) array and complementary receptors were synthesized. Two-dimensional proton nuclear magnetic resonance ((1)H NMR) measurements in CDCl(3) pointed at an intramolecular hydrogen-bond stabilization of the UAT, which promotes a planar molecular geometry and, thereby, results in a significant stabilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
4
18
0
Order By: Relevance
“…[49] Thep resence of TA enables K + [15C5] 2 one-quarter extension in lifetime (t 0 ), three-fold acceleration in the formation rate (k on ), and ad ecrease in the dissociation rate (k off ). Thes eemingly rapid k off of 62.2 and 77.0 s À1 is in fact comparable to that of supramolecular complexes (e.g.,7 .6-50 s À1 for the urea-aminotriazine pair [50,51] )a nd that of cell adhesion proteins (7-200 s À1 ). [52][53][54] Thev alues of k off for K + [15C5] 2 are actually orders of magnitude lower than those of 1-to-1 M n+ [crown] complexation (10 2 -10 7 s À1 ).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[49] Thep resence of TA enables K + [15C5] 2 one-quarter extension in lifetime (t 0 ), three-fold acceleration in the formation rate (k on ), and ad ecrease in the dissociation rate (k off ). Thes eemingly rapid k off of 62.2 and 77.0 s À1 is in fact comparable to that of supramolecular complexes (e.g.,7 .6-50 s À1 for the urea-aminotriazine pair [50,51] )a nd that of cell adhesion proteins (7-200 s À1 ). [52][53][54] Thev alues of k off for K + [15C5] 2 are actually orders of magnitude lower than those of 1-to-1 M n+ [crown] complexation (10 2 -10 7 s À1 ).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Forboth conditions,without or with the co-assembly of TA,the properties associated with mechanical rupturing are essentially the same,such as thermally induced f b and x b .T he derived barrier width, x b ( % 0.13 nm), is on the same order of magnitude as the simulated K + -O distance (0.183 nm) for K + [15C5] 2 reported in aDFT study. Thes eemingly rapid k off of 62.2 and 77.0 s À1 is in fact comparable to that of supramolecular complexes (e.g.,7 .6-50 s À1 for the urea-aminotriazine pair [50,51] )a nd that of cell adhesion proteins (7-200 s À1 ). Thes eemingly rapid k off of 62.2 and 77.0 s À1 is in fact comparable to that of supramolecular complexes (e.g.,7 .6-50 s À1 for the urea-aminotriazine pair [50,51] )a nd that of cell adhesion proteins (7-200 s À1 ).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…c o m / l o c a t e / t e t l e t coated quartz crystal chips via strong interactions between the bisthiol unit and gold. 18 To increase the hydrophilic interactions with polar solvent and the biocompatibility of isoprenoid chain, these probes had a tetraethyleneglycol (TEG) linker 19 to link isoprenoid tails and the lipoic acid moiety by an ether and ester bond, respectively (Scheme 1). Alcohols 1a-1d were treated with CBr 4 /PPh 3 to give bromides 2a-2d, which were converted to 3a-3d via Williamson etherification in good yields.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Thus DAD-ADA pairs are thermally weaker than DDD-AAA complexes [35]. In 2011 Embrechts et al showed that such cooperative effects also influences the mechanical stability of tetravalent interactions [36]. They performed DFS on UAT dimers (DADA–ADAD pairs) with UPy dimers (DDAA–AADD pairs) in hexadecane.…”
Section: Introductionmentioning
confidence: 99%